New reassortant H5N8 highly pathogenic avian influenza virus from waterfowl in Southern China - Song, Yafen; Cui, Jin; Song, Hui; Ye, Jiaqi; Zhao, Zhishan; Wu, Siyu; Xu, Chenggang; Jiao, Peirong; Liao, Ming (Frontiers in Microbiology, 2015)
New reassortant highly pathogenic H5N8 avian influenza viruses were isolated from waterfowl in Southern China. Blast analysis demonstrated that the PB2 gene in these viruses were most closely related to A/wild duck/Shangdong/628/2011 (H5N1), while their NP genes were both more closely related to A/wild duck/Shandong/1/2011 (H5N1) and A/duck/Jiangsu/k1203/2010 (H5N8). However, the HA, NA, PB1, PA, M, and NS genes had the highest homology with A/duck/Jiangsu/k1203/2010 (H5N8). Phylogenetic analysis revealed that their HA genes belonged to the same GsGd H5 clade 2.3.4.4 detected in China in 2010. Therefore, we supposed that these H5N8 viruses might be novel reassortant viruses that have a H5N8 backbone while acquiring PB2 and NP genes from H5N1 viruses. This study is useful for better understanding the genetic and antigenic evolution of H5 avian influenza viruses in Southern China.